(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the association between lifestyle habits and cardiovascular diseases among community-dwelling older adults. Methods: An analytical cross-sectional study was conducted among 6,203 older adults from eight provinces/cities in Vietnam. Associations were assessed using univariable logistic regression and a multivariable logistic regression model adjusting for selected confounders. The findings were interpreted as cross-sectional associations rather than causal effects. Results: Univariable analyses showed statistically significant associations between cardiovascular disease and older age, smoking, number of cigarettes per day, duration of smoking, alcohol use, high-salt intake, frequent consumption of animal viscera and animal fat, low fruit intake, family care, sleep disorders and several physical-activity characteristics. In the multivariable model, moderate physical activity was associated with higher odds of cardiovascular disease (adjusted OR=3.14; 95%CI: 1.24-7.90; p=0.015) compared with light activity or less. Conclusion: Several lifestyle habits and living conditions were associated with cardiovascular disease among community-dwelling older adults. These results support health education on smoking cessation, alcohol-use control, healthy diet, sleep improvement and age-appropriate physical activity.